2011
DOI: 10.1007/s12149-010-0462-y
|View full text |Cite
|
Sign up to set email alerts
|

The usefulness of fully three-dimensional OSEM algorithm on lymph node metastases from lung cancer with 18F-FDG PET/CT

Abstract: 3D-OSEM algorithm successfully improved the diagnostic accuracy of LN metastases in 3D-PET tests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 23 publications
0
4
0
Order By: Relevance
“…In OSEM2D, 3D data is generally converted into 2D data using a rebinning step such as Fourier rebinning method to reduce the reconstruction time. In the clinical field, OSEM3D reportedly improves the image quality, compared with OSEM2D [ 10 ]. In addition, OSEM3D with point spread function correction, such as OSEM3D followed by maximum a posteriori (MAP), is used in the preclinical field and has been reported to exhibit a higher uniformity, higher recovery coefficient, and lower spill over ratio than either OSEM2D or FBP [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In OSEM2D, 3D data is generally converted into 2D data using a rebinning step such as Fourier rebinning method to reduce the reconstruction time. In the clinical field, OSEM3D reportedly improves the image quality, compared with OSEM2D [ 10 ]. In addition, OSEM3D with point spread function correction, such as OSEM3D followed by maximum a posteriori (MAP), is used in the preclinical field and has been reported to exhibit a higher uniformity, higher recovery coefficient, and lower spill over ratio than either OSEM2D or FBP [ 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Rajaram et al, in their 2D PET/CT study evaluating the impact of emission-transmission misregistration on myocardial blood flow quantification, artificially created 5-and 10-mm misregistrations along both the x-axis (left) and the z-axis (cranial) such that the lung parenchyma in CT overlapped the anterior and lateral LV walls in PET (6). PET/CT systems with 3D OSEM combined with TOF and PSF modeling have been shown to significantly improve PET image quality (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(22)(23)(24)(25)(26). However, it is still unknown whether the influence of PET/CT misregistration on myocardial uptake is greater for 3D PET/CT than for 2D PET/CT.…”
Section: Discussionmentioning
confidence: 99%
“…3D PET has higher sensitivity than 2D PET, substantially improving the signal-to-noise ratio in PET images (9). Image reconstruction using 3D ordered-subset expectation maximization (OSEM) improves both spatial resolution and contrast-to-noise ratio in comparison with filtered backprojection reconstruction (10)(11)(12). In addition, recent 3D PET/CT scanners use time-of-flight (TOF) and point-spread-function (PSF) modeling, further improving spatial resolution, signal-to-noise ratio, and contrastto-noise ratio (12)(13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%
“…In 3D-OSEM algorithms, every type of correction of the 3D-acquired image data is performed within the calculation loop of successive approximations, resulting in good quality images. 5 Although previous studies have reported that 3D-OSEM algorithm can provide higher image quality than FORE þ OSEM algorithm, 6,7 they did not study image data obtained with a short acquisition time.…”
Section: Introductionmentioning
confidence: 99%